Qualitative research and theory development : mystery as method - Alvesson, Mats. (Thousand Oaks, CA : SAGE Publications, 2011)
The use of empirical material for theory development -- The role of constructions and language in empirical research -- Key methodological of sorts for theorizing from empitical material -- Illustrating the development and resolution of mysteries -- Fieldwork techniques and mystery creation -- Research guided or assisted by mystery?
Includes bibliographical references (p. [122]-130) and index.
Keywords: Social sciences -- Research -- Methodology